The inhibition of adrenal steroidogenic enzymes and modulation of glucocorticoid levels in vitro and in vivo by aspalathus linearis (rooibos) - Schloms, Lindie (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.